NK cells and ILCs in tumor immunotherapy. (August 2021) - Sivori, Simona; Pende, Daniela; Quatrini, Linda; Pietra, Gabriella; Della Chiesa, Mariella; Vacca, Paola; Tumino, Nicola; Moretta, Francesca; Mingari, Maria Cristina; Locatelli, Franco; Moretta, Lorenzo
Abstract: Cells of the innate immunity play an important role in tumor immunotherapy. Thus, NK cells can control tumor growth and metastatic spread. Thanks to their strong cytolytic activity against tumors, different approaches have been developed for exploiting/harnessing their function in patients with leukemia or solid tumors. Pioneering trials were based on the adoptive transfer of autologous NK cell-enriched cell populations that were expanded in vitro and co-infused with IL-2. Although relevant results were obtained in patients with advanced melanoma, the effect was mostly limited to certain metastatic localizations, particularly to the lung. In addition, the severe IL-2-related toxicity and the preferential IL-2-induced expansion of Treg limited this type of approach. This limitation may be overcome by the use of IL-15, particularly of modified IL-15 molecules to improve its half-life and optimize the biological effects. Other approaches to harness NK cell function include stimulation via TLR, the use of bi- and tri-specific NK cell engagers (BiKE and TriKE) linking activating NK receptors (e.g. CD16) to tumor-associated antigens and even incorporating an IL-15 moiety (TriKE). As recently shown, in tumor patients, NK cells may also express inhibitory checkpoints, primarily PD-1. Accordingly, the therapeutic use of checkpoint inhibitors may unleash NK cells against PD-L1 + tumors. This effect may be predominant and crucial in tumors that have lost HLA cl-I expression, thus resulting "invisible" to T lymphocytes. Additional approaches in which NK cells may represent an important tool for cancer therapy, are to exploit the unique properties of the "adaptive" NK cells. These CD57 + NKG2C + cells, despite their mature stage and a potent cytolytic activity, maintain a strong proliferating capacity. This property revealed to be crucial in hematopoietic stem cell transplantation (HSCT), particularly in the haplo-HSCT setting, to cure high-risk leukemias. T depleted haplo-HSCT (e.g. from one of the parents) allowed to save the life of thousands of patients lacking a HLA-compatible donor. In this setting, NK cells have been shown to play an essential role against leukemia cells and infections. Another major advance is represented by chimeric antigen receptor (CAR)-engineered NK cells. CAR-NK, different from CAR-T cells, may be obtained from allogeneic donors since they do not cause GvHD. Accordingly, they may represent "off-the-shelf" products to promptly treat tumor patients, with affordable costs. Different from NK cells, helper ILC (ILC1, ILC2 and ILC3), the innate counterpart of T helper cell subsets, remain rather ambiguous with respect to their anti-tumor activity. A possible exception is represented by a subset of ILC3: their frequency in peri-tumoral tissues in patients with NSCLC directly correlates with a better prognosis, possibly reflecting their ability to contribute to the organization of tertiary lymphoid structures, an important site of T cell-mediated anti-tumor responses. It is conceivable that innate immunity may significantly contribute to the major advances that immunotherapy has ensured and will continue to ensure to the cure of cancer.